State-Owned Enterprises (SOEs) in Construction Services in Indonesia - Mhod Razif Idris; Andri Hermawan (Ann Publisher, 2025)
Background. The construction industry plays a strategic role in Indonesia’s economic development, particularly through State-Owned Enterprises (SOEs) that are mandated to deliver national infrastructure projects. Despite their importance, Indonesian construction SOEs continue to face persistent challenges, including low productivity, cost overruns, schedule delays, bureaucratic complexity, and limited organizational agility. Lean Management has been widely recognized as a practical approach to improving efficiency and reducing waste; however, its application in the construction sector has predominantly focused on project-level operations rather than organizational-level readiness. Aims. This study aims to identify the key factors influencing the successful implementation of Lean Management in Indonesian construction SOEs and to assess how these factors interact in determining organizational readiness. Methods. A quantitative research design was employed, with a structured survey administered to 246–250 respondents from six major Indonesian construction SOEs. The study adopts the Lean Construction Maturity Model (LCMM), consisting of 11 main attributes: lean leadership, customer focus, organizational culture, competency, process and tools, change management, work environment, business results, and learning and competency development. Data were analyzed using linear regression to examine relationships among influencing factors and their contribution to Lean Management readiness. Result. The findings are expected to yield a Lean Management Implementation Readiness Index that provides a comprehensive measure of organizational preparedness and highlights critical interdependencies among factors. Conclusion. The study contributes theoretically by extending lean management research to the organizational level within construction SOEs and practically by offering a diagnostic tool to support strategic decision-making, policy formulation, and performance improvement in Indonesia’s construction sector.